Workshop on strengthening character education strategies at SD IT Sabilul Qur'an Cendekia - Aiman Faiz; Aris Fadly; Mitia Arizka Wardani (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Strengthening character education is a necessity today, considering that humans are in the 21st century where at this time technology is increasingly advanced and the obstacles, the challenges are increasingly complex. The purpose of this service is to provide knowledge related to moral and character education strategies given to 12 teachers at SD IT Sabilul Quran Cendekia in Cirebon City. The implementation of the research consists of the preparation stage; implementation stage; monitoring and evaluation stage. Based on the results of the workshop activities, there is an understanding and improvement of teacher knowledge related to moral and character education strategies. The teacher initially only understood that the cultivation of moral values and character-building could only be done by transmitting values that emphasized indoctrination. The conclusion from this workshop activity is that the development of moral and character education strategies in the 21st century requires various innovations because the challenges and obstacles to moral and character education are changing and differing from era to era. For this reason, teachers need to be given a variety of knowledge to be able to overcome various problems encountered during the educational process. This workshop is one of the efforts of teachers to open their minds so that they can be better prepared to face the challenges of education in this century